Techno-economic assessment of wind power generation feasibility in Sabang - Zulfaini Zulfaini; Adi Setiawan; Muhammad Daud (Jurnal POLIMESIN, 2023)
Utilization of renewable energy in Aceh is still limited mainly to small-scale electricity through micro-hydro and solar power plants, accounting for less than 1% of the energy composition. Sabang stands out as a region with significant wind energy potential, boasting a speed of 8 m/s and an average power density of 537 W/m2 for the windiest 10% of the region. Therefore, to explore the viability of harnessing wind energy, a pre-feasibility study is needed. This study aimed to assess the techno-economic feasibility of constructing a wind power plant for electricity generation in Sabang by evaluating the region's wind energy. The statistical method of the Weibull Distribution probability density function was employed to evaluate Wind Power Density (WPD), Wind Turbine Capacity Factor, and Energy Output. Additionally, economic feasibility analysis involved calculating Net Present Value (NPV), Benefit Cost Ratio (BCR), Internal Rate of Return (IRR), Discounted Payback Period (DPP), and Levelized Cost of Energy (LCOE). The results showed that Sabang exhibited favorable[UMN1]  wind characteristics with a shape parameter (k) of 1.6, average wind speed (Vm) of 7.9 m/s, and scale parameter (c) of 9 m/s. These features classified Sabang as wind power class 6 with a WPD of 735 watts/m2 at a height of 50 m, and the results were categorized as excellent. The study concluded that constructing a wind power plant in Sabang using the Enercon E-70 turbine at a hub height of 100m was technically feasible. The shape parameter (k) was 1.6, the average wind speed (Vm) was 9.3 m/s, scale parameter (c) was 11 m, and the WPD reached 1213 W/m2, leading to a turbine capacity factor of 0.53 and an annual energy production (AEP) of 64,876,560 kW. The economic analysis yielded promising results for wind power projects. The DPP value was estimated at 5.6 years, the BCR at 1.96, the NPV amounted to USD 14,434,994, the IRR reached 17.9%, and the LCOE was assessed at USD 32.50/MWh. Considering all these economic indicators, it was evident that constructing a wind power plant in Sabang was highly feasible and financially viable